MODEL PEMBELAJARAN AKTIF KREATIF EFEKTIF MENYENANGKAN MELALUI PENDEKATAN TEMATIK UNTUK PEMBELAJARAN SAINS SEKOLAH DASAR - Ernawati Saptaningrum; Fine Reffiane (Universitas PGRI Semarang, 2011)
Abstrak?é?áThe purpose of this study are as follows: 1) the development of elementary science materials with a thematic approach, 2) development of learning strategies grip with a thematic approach to elementary science, 3) development of evaluation instruments thematic learning elementaryschoolscience.This research is the Research and Development which aims to develop devices with a model elementary school science learning through a thematic approach PAKEM. The subject of this study were elementary school students from groups I and II, public school, private elementary Favorite groups and groups of private elementary school, two teachers and class I and class II. The research was done in the city of Semarang.Research activities in this first year begins with elementary curriculum analysis and analysis of the needs of students in accordance with aspects of the development of elementary school children, followed by identification of the material associated with the appropriate science curriculum and describe the science of learning support facilities required, step three made the development of material science SD with PAKEM through a thematic approach, to a four-step development of learning strategies in inquiry activities here are designed with PAKEM through pendekatn Thematic Science Elementary School, and the fifth step is the development of evaluation tools in the form of assessment of cognitive, affective and psychomotor.Based on the first tahiun research activities, overall these studies have been done 70%. The next test will be conducted so that the experts and get a draft revision of elementary school science materials, learning tools which include SKH, SKM, and RPP, as well as an evaluation tool in elementary science pembejaran PAKEM with a thematic approachKeywords: PAKEM, Thematic, SD